Breaking the blisters: a comprehensive guide to treating bullous pemphigoid - Subhan, Amber; Siddhartha, Lolla; Goud, Mudimala Rekha; Khanam, Safura (International Journal of Basic & Clinical Pharmacology, 2025)
In adapting the treatment plan, the severity of the disease in correlation with the patient should be put onto consideration. Recent RCTs demonstrated adjuvant treatment with doxycycline, dapsone, and immunosuppressants for the treatment of bullous pemphigoid is of advantage and safe in terms of diminished total steroid dose and mortality. The British association of dermatologists has produced dermatologists’ guidelines. These provide evidence-based treatment recommendations with respect to candidness, and offer a summary on, among others, epidemiological features, diagnosis, and research. The evidence on which the guidelines rest was retrieved from Medline, Embase, the Cochrane Library, literature searches, and the authors’ 10 years of experience treating patients with bullous pemphigoid in general and special clinics. However, it should be noted that findings from the literature should be interpreted with great care as only six randomized controlled trials with small patient groups are available.